Increasing Dose of Autologous Bone Marrow Mononuclear Cells Transplantation Is Related to Stroke Outcome: Results from a Pooled Analysis of Two Clinical Trials - Francisco Moniche; Paulo Henrique Rosado-de-Castro; Irene Escudero; Elena Zapata; Francisco Javier de la Torre Laviana; Rosalia Mendez-Otero; Magdalena Carmona; Pilar Piñero; Alejandro Bustamante; Lucía Lebrato; Juan Antonio Cabezas; Alejandro Gonzalez; et al. (Stem Cells International)
Background and Purpose. BM-MNC transplantation improves recovery in experimental models of ischemic stroke. Clinical trials are ongoing to test efficacy in stroke patients. However, whether cell dose is related to outcomes is not known. Methods. We performed a pooling data analysis of two pilot clinical trials with autologous BM-MNCs transplantation in ischemic stroke patients. Cell dose and route were analyzed to evaluate their relation to good outcome (m-Rankin scale [mRS] score 0–2) at 6 months. Results. Twenty-two patients were included. A median of 153 × 106 (±121 × 106) BM-MNCs was injected. Intra-arterial route was used in 77.3% of cases. A higher number of cells injected were associated with better outcomes at 180 days (390 × 106 [320–422] BM-MNCs injected in those patients with mRS of 0–2 at 6 months versus 130 × 106 [89–210] in those patients with mRS 3–6, p=0.015). In the intra-arterially treated patients, a strong correlation between dose of cells and disability was found (r=-0.63, p=0.006). A cut point of 310 × 106 injected cells predicted good outcome with 80% sensitivity and 88.2% specificity. Conclusions. Similar to preclinical studies, a higher dose of autologous BM-MNC was related to better outcome in stroke patients, especially when more than 310 × 106 cells are injected. Further interventional studies are warranted to confirm these data.